2019
DOI: 10.1111/jdv.16088
|View full text |Cite
|
Sign up to set email alerts
|

Safe and effective use of alitretinoin in children with recalcitrant hand eczema and other dermatoses – a retrospective analysis

Abstract: Background Alitretinoin is a systemic retinoid licensed for use in adult patients suffering from chronic hand eczema recalcitrant to potent topical steroids. Experience with its use in childhood is lacking.Objectives To report on the efficacy and safety of alitretinoin treatment in a cohort of children and adolescents with chronic hand eczema (CHE) and other inflammatory skin diseases. MethodsWe performed a retrospective chart review of all consecutive patients under the age of 18 years treated with alitretino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…The youngest patients were a few months old, the oldest patient was 43 years of age. In two patients, age was not reported ( 50 , 67 ). 25 patients were male and 20 patients were female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The youngest patients were a few months old, the oldest patient was 43 years of age. In two patients, age was not reported ( 50 , 67 ). 25 patients were male and 20 patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…In 18 patients simultaneous use of topical treatments including corticosteroids was reported during treatment with the systemic agents (see Table 1 ). 7 patients received multiple systemic treatments for NS simultaneously which sometimes prevented interpretation of treatment results ( 38 , 56 , 65 , 67 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…6 Another study of 9 children with P-CHE found an average Hand Eczema Severity Index score correlating to severe disease before initiation of alitretinoin therapy; however, there was selection bias because all children failed multiple therapies before starting alitretinoin. 25,26 These 6 studies constitute the bulk of the literature on the signs, symptoms, disease course, and outcomes in pediatrics. Hand eczema studies in adults show that the disease process presents with edema, erythema, or vesiculation in its acute form, and fissuring, scaling, or crusting chronically.…”
Section: Symptoms Distribution and Morphologymentioning
confidence: 99%
“…Auch beim Handekzem bei Kindern zeigt sich ein sehr gutes Ansprechen. Allerdings entwickelten Dreiviertel der Kinder in dieser kleinen Pilotstudie (N = 13) Kopfschmerzen [35]. Das Acitretin, das seine Wirkung nur über den RA-Rezeptor entfaltet, ist im Vergleich zum Alitretinoin und Ciclosporin in die dritte Reihe gerückt.…”
Section: Systemtherapienunclassified